2015
DOI: 10.1088/0004-6256/150/5/155
|View full text |Cite
|
Sign up to set email alerts
|

The Cluster Ages Experiment (Case). Vii. Analysis of Two Eclipsing Binaries in the Globular Cluster NGC 6362

Abstract: We use photometric and spectroscopic observations of the detached eclipsing binaries V40 and V41 in the globular cluster NGC 6362 to derive masses, radii, and luminosities of the component stars. The orbital periods of these systems are 5.30 and 17.89 d, respectively. The measured masses of the primary and secondary components (M p , M s ) are (0.8337±0.0063, 0.7947±0.0048) M ⊙ for V40 and (0.8215±0.0058, 0.7280±0.0047) M ⊙ for V41. The measured radii (R p , R s ) are (1.3253±0.0075, 0.997±0.013) R ⊙ for V40 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Interestingly, both figures give the impression that V40 and V41 follow somewhat different M-R relations, even on the (log T eff , M V )-plane despite the large error bars attached to the derived temperatures. Kaluzny et al (2015) noticed the same thing, but whereas they tentatively suggested that this was due to a ∼ 1.5 Gyr age difference, the more likely explanation is that V40 has a slightly lower initial helium abundance than V41 (by only ∆Y ∼ 0.007) given that the cluster HB shows unambiguous evidence for a much larger spread in Y .…”
Section: 4mentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, both figures give the impression that V40 and V41 follow somewhat different M-R relations, even on the (log T eff , M V )-plane despite the large error bars attached to the derived temperatures. Kaluzny et al (2015) noticed the same thing, but whereas they tentatively suggested that this was due to a ∼ 1.5 Gyr age difference, the more likely explanation is that V40 has a slightly lower initial helium abundance than V41 (by only ∆Y ∼ 0.007) given that the cluster HB shows unambiguous evidence for a much larger spread in Y .…”
Section: 4mentioning
confidence: 92%
“…The masses and radii of the detached eclipsing binary in M 55 (known as V54) have been derived to within 2.1% and 0.95%, respectively, by Kaluzny et al (2014). The same group (see Kaluzny et al 2015) have been able to measure the masses of the components of two detached eclipsing binaries, V40 and V41, in NGC 6362 to better than 0.71%, as compared with radius uncertainties of < 1.3%. Mean magnitudes and colors of the 15 RR Lyrae variables that have been found in M 55 are provided by Olech et al (1999), who also measured these quantities in the nearly three dozen RR Lyrae that reside in NGC 6362 (Olech et al 2001).…”
Section: The [Fe/h] Values Derived Bymentioning
confidence: 98%
“…The methods and assumptions we employ follow the ideas of Paczyński (1997) and Thompson et al (2001); more details can be found in Kaluzny et al (2002). Thus far, we have presented results for eight binaries with MS or SG components in four GCs: 47 Tuc (Thompson et al 2010, hereafter TK10), M4 (Kaluzny et al 2013b), M55 ) and NGC 6362 (Kaluzny et al 2015). These are the first and, to the best of our knowledge, the only direct measurements of the fundamental parameters of such stars in GCs.…”
Section: Introductionmentioning
confidence: 97%
“…Our PMs are clearly in consistence with those presented by Zl12 up to 20 V mag. Kaluzny et al (2015) and the UV variables found in GUVV2 catalog (ID V (UV ) . ID represents the corresponding star number in our catalog.…”
Section: Comparison With Zl12mentioning
confidence: 99%